Advances in geomorphology and quaternary studies in Argentina : proceedings of the Sixth Argentine Geomorphology and Quaternary Studies Congress - Rabassa, Jorge (Springer, 2017)
This proceedings volume presents selected research highlights from the Sixth Argentine Geomorphology and Quaternary Studies Congress, hosted at CADIC, Ushuaia, on April 8-12, 2015 by the Argentine Association of Geomorphology and Quaternary Studies (AACYG). The congress included special sessions, symposia, invited lectures and posters on the following topics: Quaternary stratigraphy and geochronology, paleontology (diatoms, mollusks, foraminifera, palynology, phytoliths, paleobotany, vertebrates), dendrochronology, climate change, paleoclimate, Pampean Quaternary paleolimnology, paleomagnetism, environmental magnetism, hydrogeochemical processes, geoarchaeology, geomorphology, structural geology and neotectonics, paleosurfaces, volcanism, geological hazards, assets, geomorphosites, and digital mapping. The Scientific Committee of the Congress has selected the papers published in this volume from more than 150 contributions in many different disciplines.
Includes index.
Keywords: Geomorphology -- Congresses.; Earth sciences -- Congresses.; elektronické knihy; electronic books